Optical, luminescence and scintillation properties of Mg2+-codoped (Lu, Y)3Al2Ga3O12:Pr garnet crystals: The effect of Y admixture. (November 2022) - Sreebunpeng, Krittiya; Chewpraditkul, Warut; Chewpraditkul, Weerapong; Yoshikawa, Akira; Witkowski, Marcin E.; Drozdowski, Winicjusz; Nikl, Martin
Abstract: Mg - codoped Lu3-x Yx Al2 Ga3 O12 :Pr (x = 0, 1, 2, and 3) garnet crystals were grown by micro-pulling down method and scintillation characteristics were investigated. An observed red shift of the Pr 3+ 5d1 → 4f luminescence with increasing Y content can be attributed to an increase in crystal field splitting of the 5d levels. Temperature dependence of radioluminescence (RL) spectra was measured in the temperature range of 10–350 K, yielding a decrease of RL yield with increasing temperature for all samples. The LuY2 Al2 Ga3 O12 :Pr, Mg exhibits light yield of 9100 photons/MeV along with two scintillation decay components of 8.6 ns (9%) and 25 ns (91%). Afterglow and thermoluminescence characteristics are also investigated. Highlights: Lu3-x Yx Al2 Ga3 O12 :Pr, Mg scintillation crystals were grown by micro-pulling down method. Lu3-x Yx Al2 Ga3 O12 :Pr, Mg (x = 2, 3) exhibit high integral scintillation efficiency ∼ 330% of BGO crystal. LuY2 Al2 Ga3 O12 :Pr, Mg exhibits light yield of 9100 photons/MeV and fast effective decay time of 23.5 ns.